(untitled) (Global Journal of Human-Social Science, 2016)
Teachers are the important pillar of education system It is also believed that teachers shape up a student s life The role of the teacher in the classroom has been found to be the single most important factor in student learning The vast majority of teachers strive to teach effectively in order to enhance student learning outcomes and they draw upon the knowledge and skills acquired throughout their preservice teacher degree The 21st century saw the role of the teacher move from one who is all-knowing and unquestionable to one who is continually learning selfaware and reflective Further teachers are now expected to encourage their students to engage in thoughtful reflection critical thinking and increased selfawareness and responsibility Every educational system in any identified human society requires highly skilled teaching staffs to raise the standard of education No educational system can rise above the quality of its teachers The Report of the Commission on National Education 1959 further adds that the teacher should be academically well-trained in subjects he she teaches and have had sound professional training to teach his her subjects In order to achieve this objective a course called B Ed Bachelor of Education was introduced This course teaches a person all about being a good teacher Once the person completes the course he she is awarded the degree and is qualified to become a full fledged teacher